ЕКСПЕРИМЕНТАЛЬНЕ ДОСЛІДЖЕННЯ ПРОЦЕСІВ НАМАГНІЧУВАННЯ ТА РОЗМАГНІЧУВАННЯ АСИНХРОННОГО ДВИГУНА З ВЕКТОРНИМ КЕРУВАННЯМ - Leidhold, R.; Калугін, Д.В.; Толочко, O.І. (Інститут електродинаміки НАН України, Київ, 2024)
Experimental research of the processes of magnetization and demagnetization for the motionless vector-controlled induction motor was performed, according to a linear law with a variation in the duration of these processes. The methodology of research during which the orthogonal components of the stator and rotor currents were recorded in the rotor flux reference frame, the rotor flux module and the energy of the total losses in the stator and rotor copper is described. The main characteristics and parameters of laboratory equipment and facilities are given. From the point of view of minimizing copper losses, the existence of the optimal duration of the investigated transient processes has been experimentally proven. The results of experimental studies with high accuracy coincide with calculations based on previously obtained analytical dependencies, which confirms the admissibility of the assumptions made during theoretical studies. References 10, figures 7, tables 2.